Respostas
respondido por:
0
B²- 4 (2s - A) (s² - C) = -8s³ + 4As² + 8Cs – 4AC + B²
B² - 4.(2s³ - 2Cs - As² + AC) = - 8s² + 4As² + 8Cs - 4AC + B²
B² - 8s² + 8Cs + 4As² - 4AC = - 8s² + 4As² + 8Cs - 4AC + B²
B² - 8s² + 8Cs + 4As² - 4AC + 8s² - 4As² - 8Cs + 4AC - B² =
B² - B² - 8s² + 8s² + 8Cs - 8Cs + 4As² - 4As² - 4AC + 4AC = cancela todos
0
B² - 4.(2s³ - 2Cs - As² + AC) = - 8s² + 4As² + 8Cs - 4AC + B²
B² - 8s² + 8Cs + 4As² - 4AC = - 8s² + 4As² + 8Cs - 4AC + B²
B² - 8s² + 8Cs + 4As² - 4AC + 8s² - 4As² - 8Cs + 4AC - B² =
B² - B² - 8s² + 8s² + 8Cs - 8Cs + 4As² - 4As² - 4AC + 4AC = cancela todos
0
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás